2021
DOI: 10.1016/j.jaim.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of a standardized Curcuma longa Linn formulation in cervical cancer

Abstract: Background The anti-cancer activity of phytomolecules present in turmeric or haridra ( Curcuma longa Linn) extracts against cancer has been described in various ‘ in vitro and in vivo’ studies. Objective In the present study, in vitro and in vivo anti-cancer and chemo-preventive activity of a new standardized S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Regarding cervical cancer, oral TO pre-treatment in mice with tumor xenograft implants displayed a chemopreventive effect by decreasing tumor size (p = 0.163). In vitro, no cytotoxic effect was observed in three cancer cell lines (HeLa, SiHa, and ME180) with a maximum concentration of 80 µg/mL [38]. Conversely, another study reported TO's cytotoxicity against HeLa cells at higher concentrations (2100 µg/mL).…”
Section: Anticancermentioning
confidence: 88%
See 1 more Smart Citation
“…Regarding cervical cancer, oral TO pre-treatment in mice with tumor xenograft implants displayed a chemopreventive effect by decreasing tumor size (p = 0.163). In vitro, no cytotoxic effect was observed in three cancer cell lines (HeLa, SiHa, and ME180) with a maximum concentration of 80 µg/mL [38]. Conversely, another study reported TO's cytotoxicity against HeLa cells at higher concentrations (2100 µg/mL).…”
Section: Anticancermentioning
confidence: 88%
“…Nevertheless, the exact contribution of antioxidants supplementation as adjuvants in radiotherapy and certain types of chemotherapy remains unclear to date [42]. Since TO's capability to affect the viability and morphological changes in cervical cancer cells and control tumor size corresponds to a dose-dependent relationship, it is advisable to determine the therapeutical index to better understand its antitumor activity [38,39].…”
Section: Anticancermentioning
confidence: 99%